Vascular risk factors for male and female urgency urinary incontinence at age 68 years from a British birth cohort study. (7th March 2018) - Tsui, Alex; Kuh, Diana; Cardozo, Linda; Davis, Daniel
Abstract : Objective: To investigate the prevalence of urgency urinary incontinence (UUI) at age 68 years and the contribution of vascular risk factors to male and female UUI pathogenesis in addition to the associations with raised body mass index (BMI). Subjects and methods: In all, 1 762 participants from the Medical Research Council (MRC) National Survey for Health and Development birth cohort who answered the International Consultation on Incontinence Questionnaire short form (ICIQ‐SF), at age 68 years, were included. Logistic regression was used to estimate associations between UUI and earlier life vascular risk factors including: lipid status, diabetes, hypertension, BMI, previous stroke or transient ischaemic attack (TIA) diagnosis; adjusting for smoking status, physical activity, co‐presentation of stress UI symptoms, educational attainment; and in women only, type of menopause, age at period cessation, and use of hormone replacement therapy (HRT). Results: UUI was reported by 12% of men and 19% of women at age 68 years. Female sex, previous stroke or TIA diagnosis, increased BMI and hypertension (in men only) at age 60–64 years were independent risk factors for UUI. Female sex, increased BMI, and a previous diagnosis of stroke/TIA increased the relative risk of more severe UUI symptoms. Type and timing of menopause and HRT use did not alter the estimated associations between UUI and vascular risk factors in women. Conclusion: Multifactorial mechanisms lead to UUI and vascular risk factors may contribute to the pathogenesis of bladder overactivity in addition to higher BMI. Severe UUI appears to be a distinct presentation with more specific contributory mechanisms than milder UUI.